New Insights into Health Conditions Related to Malfunctions in Clock Genes - Kaja Majewska; Mikołaj Seremak; Katarzyna Podhorodecka; Maria Derkaczew; Bartosz Kędziora; Paulina Boniecka; Kamila Zglejc-Waszak; Agnieszka Korytko; Małgorzata Pawłowicz; Joanna Wojtkiewicz (Biomolecules)
Chronotypes play a crucial role in regulating sleep–wake cycles and overall health. The aim of this study was to investigate chronotype, sleep quality, polymorphisms of clock genes and the level of leptin in serum. We used standardized questionnaires to assess chronotype and sleep quality. Genetic analysis was performed to determine the selected clock gene polymorphism. Serum leptin level was measured by the Elisa method. The results showed that serum leptin concentration was elevated in women, as well as in men who had a high waist-to-hip ratio (WHR) and body mass index (BMI). The evidence indicated that younger students (<22 years old) were most likely to experience poor sleep quality. Nevertheless, our multivariate analysis revealed that young age and a morning-oriented chronotype were associated with better sleep quality. We noted that clock gene polymorphisms were present in 28.6% of the participants. Moreover, polymorphisms of PER1 c.2247C>T (rs2735611) and PER2 c.-12C>G (rs2304672) genes were associated with serum leptin level and chronotype, respectively. These findings provide insights into the relationships between chronotype, sleep quality, clock gene polymorphisms and obesity risk in biomedical students. Understanding these factors can contribute to better sleep management and potential interventions to improve health outcomes in humans.